Silicon-based soft parallel robots 4D printing and multiphysics analysis - Zolfagharian, Ali; Gharaie, Saleh; Kouzani, Abbas Z; Lakhi, Mohammad; Ranjbar, Sadegh; Lalegani Dezaki, Mohammadreza; Bodaghi, Mahdi (Smart materials and structures, 2022)
Four-dimensional printing has set the stage for a new generation of soft robotics. The applications of rigid planar parallel robotic manipulators are also significant because of their various desirable characteristics, such as lower inertia, higher payload, and high accuracy. However, rigid planar parallel robots are heavy and require different actuators and components. This study introduces a novel technique to produce a light three degrees of freedom soft parallel manipulator at a low cost, which can be stimulated easily. This technique allows researchers to customize the actuator’s design based on the requirement. The robot is made by 3D printing based on fused deposition modelling and a direct ink writing process. The design, development, and additive manufacturing of a soft parallel robot electrothermally driven by a linear silicon-based actuator and polylactic acid parts are presented. Silicon-based soft actuators replace the rigid conventional linear actuators in this study to drive the planar parallel manipulator. The actuation of actuators is conducted using simple heating compared to the conventional rigid actuator. Various heating approaches and configurations are compared and analysed to find the most suitable one for the effective linear stroke of the soft actuator. The finite element model is used to analyse the performance of the electrothermally silicon-ethanol soft actuators in ABAQUS. The kinematics of the planar parallel robotic manipulator are simulated in MATLAB to achieve its workspace. The final soft parallel robot mechanism and the active and passive links are fabricated and tested experimentally.